Target Deconvolution Efforts on Wnt Pathway Screen Reveal Dual Modulation of Oxidative Phosphorylation and SERCA2. (26th April 2017) - Casás‐Selves, Matias; Zhang, Andrew X.; Dowling, James E.; Hallén, Stefan; Kawatkar, Aarti; Pace, Nicholas J.; Denz, Christopher R.; Pontz, Timothy; Garahdaghi, Farzin; Cao, Qing; Sabirsh, Alan; Thakur, Kumar; et al.
Abstract: Wnt signaling is critical for development, cell proliferation and differentiation, and mutations in this pathway resulting in constitutive signaling have been implicated in various cancers. A pathway screen using a Wnt‐dependent reporter identified a chemical series based on a 1, 2, 3‐thiadiazole‐5‐carboxamide (TDZ) core with sub‐micromolar potency. Herein we report a comprehensive mechanism‐of‐action deconvolution study toward identifying the efficacy target(s) and biological implication of this chemical series involving bottom‐up quantitative chemoproteomics, cell biology, and biochemical methods. Through observing the effects of our probes on metabolism and performing confirmatory cellular and biochemical assays, we found that this chemical series inhibits ATP synthesis by uncoupling the mitochondrial potential. Affinity chemoproteomics experiments identified sarco( endo )plasmic reticulum Ca 2+ ‐dependent ATPase (SERCA2) as a binding partner of the TDZ series, and subsequent validation studies suggest that the TDZ series can act as ionophores through SERCA2 toward Wnt pathway inhibition. Abstract : Waste not, Wnt not : We identified a 1, 2, 3‐thiadiazole‐5‐carboxamide chemical series in a Wnt pathway inhibition screen. We generated chemical probes to identify the targets of this series based on our efforts to optimize potency and physical properties. Using a combination of biochemical, cell biology, and chemoproteomics methods, we found two previously unreported mechanisms for this pharmacophore: uncouplers of the mitochondrial potential and Ca 2+ ionophores through interaction with SERCA2.